Arrhythmic Mitral Valve Prolapse: New Menaces of the Known Disease - D. A. Kuzhel; G. V. Matyushin; E. A. Savchenko (Рациональная фармакотерапия в кардиологии)
Mitral  valve prolapse  (MVP) has  long  been  the subject  of intense  discussions regarding the prognosis and  follow-up tactics.  In most  cases,  this condition has a benign prognosis. However, recent autopsy and follow-up studies have shown risks of developing  sudden cardiac death (SCD) in some subgroups of patients who have this clinical phenomenon. The proposed  literature review uses the population  of patients with MVP with the highest probability  of developing  life-threatening ventricular tachyarrhythmias. Patients with the presence of a complex  of changes, including  bicuspid  MVP, negative T waves in the inferior and lateral leads on a standard  12-lead electrocardiogram (ECG), and a special anatomical  phenomenon called mitral annular  disjunction  (MAD), are at high  risk of developing  ventricular  ectopias  and VSS.  A reflection  of the high  risk of SCD  in such patients  is the increase of ventricular ectopy according to Holter monitoring. The presence of a bicuspid  MVP and the MAD  phenomenon, which is a separation  of the line of attachment  of the posterior mitral leaflet from the basal inferior wall segment  towards  the atrial wall, determines the presence of a special form of MVP,  the so-called  arrhythmogenic MVP.  Hence,  in most cases MVP has a benign  prognosis. However, patients with the aforementioned ar- rhythmic  MVP  signs  must  be given  particular  attention  and  annual  follow-up including  ECG  control,  Holter  monitoring and  echocardiographic examination of the heart to reduce the risk of ventricular tachyarrhythmias and SCD development.